Enterochromaffin Cells: Sentinels to Gut Microbiota in Hyperalgesia? - Xu, Xiaolin; Chen, Rongmin; Zhan, Gaofeng; Wang, Danning; Tan, Xi; Xu, Hui (Frontiers in Cellular and Infection Microbiology, 2021)
In recent years, increasing studies have been conducted on the mechanism of gut microbiota in neuropsychiatric diseases and non-neuropsychiatric diseases. The academic community has also recognized the existence of the microbiota-gut-brain axis. Chronic pain has always been an urgent difficulty for human beings, which often causes anxiety, depression, and other mental symptoms, seriously affecting people’s quality of life. Hyperalgesia is one of the main adverse reactions of chronic pain. The mechanism of gut microbiota in hyperalgesia has been extensively studied, providing a new target for pain treatment. Enterochromaffin cells, as the chief sentinel for sensing gut microbiota and its metabolites, can play an important role in the interaction between the gut microbiota and hyperalgesia through paracrine or neural pathways. Therefore, this systematic review describes the role of gut microbiota in the pathological mechanism of hyperalgesia, learns about the role of enterochromaffin cell receptors and secretions in hyperalgesia, and provides a new strategy for pain treatment by targeting enterochromaffin cells through restoring disturbed gut microbiota or supplementing probiotics.